2020
DOI: 10.1016/j.omto.2020.09.008
|View full text |Cite
|
Sign up to set email alerts
|

S119N Mutation of the E3 Ubiquitin Ligase SPOP Suppresses SLC7A1 Degradation to Regulate Hepatoblastoma Progression

Abstract: A previous study on hepatoblastoma revealed novel mutations and cancer genes in the Wnt pathway and ubiquitin ligase complex, including the tumor suppressor speckle-type BTB/POZ (SPOP). Moreover, the SPOP gene affected cell growth, and its S119N mutation was identified as a loss-of-function mutation in hepatoblastoma. This study aimed to explore more functions and the potential mechanism of SPOP and its S119N mutation. The in vitro effects of SPOP on cell proliferation, invasion, apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Accumulating evidence suggests that SLC7A members that encode amino acid and glucose transporters may be therapeutic targets in cancers. SLC7A1 has been suggested as a promising therapeutic target for colorectal cancers (36), hepatoblastomas (37), BC cell lines (19), pediatric sarcomas, and brain tumors (38).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that SLC7A members that encode amino acid and glucose transporters may be therapeutic targets in cancers. SLC7A1 has been suggested as a promising therapeutic target for colorectal cancers (36), hepatoblastomas (37), BC cell lines (19), pediatric sarcomas, and brain tumors (38).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of CD62L targeted drugs and immunotherapy is viable in enhancing the antitumor e cacy [39]. SLC7A1 is a transporter that responsible for the uptake of cationic amino acids uptake function, and such function is essential for cellular growth [40]. At present, studies on these IRG genes in osteosarcoma is less reported.…”
Section: Discussionmentioning
confidence: 99%
“…The SPOP substrates in these cancers include: ERα [ 35 , 95 ], and BRD 2/3/4 in endometrial cancer [ 19 ], ERα [ 96 ], PR [ 37 ], SRC3 [ 25 ], c-MYC [ 36 ], BRMS1 [ 38 ], ASCT2 in breast cancer [ 97 ], Gli2 in gastric cancer [ 98 ], Gli2 [ 99 ], HDAC6 in colorectal cancer (CRC) [ 100 ], and MyD88 and CHAF1A in diffuse large B-cell lymphoma (DLBLC) [ 101 , 102 , 103 , 104 ]. Fas-associated death domain protein (FADD) [ 105 ], SIRT2 in lung cancer (LC) [ 106 ], SENP7 in hepatocellular carcinoma (HCC) [ 107 ], DHX9 in choriocarcinoma [ 108 ], FLI1 in Ewing sarcoma [ 109 ], and SLC7A1 [ 110 ], DRAK1 and PIPKIIβ in cervical cancer (CC) [ 111 , 112 ]. Figure 3 b summarizes the different SPOP substrates and their functions in cellular processes reported in different cancers.…”
Section: Sop Expression In the Development Progression And Treatment ...mentioning
confidence: 99%